Phenomenological theory of phase transitions in the MPB region of (1−x)Pb(Mg1/3Nb2/3)O3-xPbTiO3 single crystals. (3rd May 2020) - Jang, Kum-Ok; Kim, Il-Hwan; Kim, Il-Hun; Im, Sok-Gil; Sin, Kye-Ryong; Kim, Chol-Jin
ABSTRACT: A higher-order Landau–Ginzburg–Devonshire theory is proposed to describe phenomenologically the complex phase transitions in the MPB region of the relaxor ferroelectric (1− x )Pb(Mg1/3 Nb2/3 )O3 - x PbTiO3 (PMN-PT) single crystals. Using the singularity theory, a structurally stable 10th-order potential with four varying expansion coefficients ( a 1, a 11, a 2 and a 12 ) depending on temperature and composition is found out. By studying on two- and three-dimensional sections of a four-dimensional phase diagram a 1 - a 11 - a 2 - a 12 in the space of phenomenological parameters, the range of coefficient parameters by which the structural stability of the potential model can be guaranteed is determined. The theoretical temperature-composition phase diagram is constructed and it is shown that this is in good agreement with both recent experimental data and first-principle calculation for the symmetry change. Moreover, temperature dependence of dielectric constants for various compositions is studied.